PENGARUH KERJASAMA TIM DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA SURABAYA - Hidajat, Agus (Seminar Nasional Manajemen, 2025)
Abstract This study aims to determine the influence of teamwork and work discipline on employee performance at the Human Resources and Personnel Agency (BKPSDM) of Surabaya City. A quantitative associative approach was used, with data collected via questionnaires from 35 employees. The results showed that both teamwork and work discipline had positive and significant impacts on employee performance, both partially and simultaneously. Teamwork enhanced collaboration, mutual responsibility, and optimal contributions, while work discipline fostered efficiency, adherence to rules, and accountability. These findings suggest that BKPSDM should reinforce collaborative culture and implement consistent disciplinary measures to improve employee performance. Keywords: teamwork; work discipline; performance; employees; public sector